EFEKTIFITAS PENERAPAN HEALTH BELIEF MODELTERHADAP PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) - Priyo, Priyo; Priyanto, Sigit (Universitas Muhammadiyah Magelang, 2018)
The degree of human health can be influenced by behavior. This behavior factor still becomes a health problem in Indonesia. Unhealthy behavior causes various kinds of infectious diseases and non-infectious diseases. Various efforts to change the behavior of people who do not know, do not want to, and cannot afford it, have been carried out t by the government. However, Clean and Healthy Behavior is still a concern and not optimal yet. Health Belief Model (HBM) is applied as a model in efforts to overcome PHBS. The purpose of this study was to identify the effectiveness of the application of Health Belief Model to PHBS. This research is a quasy experiment with the design of one group pre-post test design. The population in this study was 40 respondents. The method of sampling used was purposive sampling method. The treatment was carried out once per week for 3 weeks. The results showed a difference in the effect of Health Belief Model (HBM) on Clean and Healthy Life Behavior (PHBS). The results of the Wilcoxon test analysis for 3 interventions in 3 weeks showed: the knowledge of PHBS (p ^ 0.00), the attitude of PHBS (0.01) and PHBS Behavior (p ^ 0.00), which means there are differences in the effect of changes in knowledge, attitudes and behavior of PHBS after HBM intervention. Health workers, especially nurses, are expected to make HBM as an effort to promote health and change hygienic and healthy living behavior in families or communities.